Quality of Elderly People’s Life in the Region of Malopolskie Voivodship - Kowalska, Magdalena Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The ageing of the population is one of the most important problems of contemporary European societies. It is assumed that, within the next two decades, the percentage of people aged 65 and older throughout the population of the European Union will increase up to 20%, and around 2060 – nearly one third of the community’s inhabitants will reach this age. Therefore, it is important for the elderly people to have proper living conditions ensured, in particular in countries such as Poland, where seniors are still marginalised and excluded from many areas of social life. The quality of life of people in the post‑working age can be determined by taking account of numerous factors. These include, above all: financial situation, living conditions, health condition, self‑esteem, and the feeling of playing a significant role for the family and for the society. The purpose of the presented study is to assess the quality of life of elderly people from the region of Malopolskie Voivodship. The analysis of the research material takes account of various aspects of this particular category, namely the quality of life, with clear focus on the so‑called subjective quality of life. Conclusions were drawn on the basis of results of the study conducted in 2015 on a group of 150 people aged 60+, living in the counties of Myślenice and Nowy Targ from the Małopolskie Voivodship. Among numerous elements that can be used to assess the quality of life, crucial importance has the determination of the degree of satisfaction of seniors on several levels: with regard to relations with family members, health condition, and the housing situation. In addition, it was deemed important to identify the attitude of the environment towards seniors, as well as indicate the needs and expectations of elderly people with regard to e.g. services and products missing from the Polish market and addressed to this age category. The research results indicate that the subjective quality of life of the examined elderly people from the two counties is on an average level. Such a conclusion may be drawn on the basis of opinions of the respondents, who are rather satisfied with contacts with the environment and, at the same time, moderately satisfied with their health condition. Furthermore, the examined seniors notice clear shortages on the Polish market within the offer of services and products addressed specifically to their age group.